THE COMPOUND ORIGIN OF POTENTIAL IN A STIMULATED DORSAL ROOT - Eisenman, George (The Rockefeller University Press, 1954)
The electrotonic potential appearing in a stimulated dorsal root is found to be the resultant of two independent systems of current of different origin. One component, labelled DRα, is non-occluding. The other component, labelled DRβ, occludes strongly and has the characteristics of the potential which appears in a neighboring unstimulated rootlet (DRIV-V). Because DRα does not occlude, its origin is assigned to the primary afferent neuron. The result of a general examination of its origin leads to the additional conclusion that it must arise from a physiological spatial gradient in the post-spike recovery cycle of membrane potential along the afferent neuron. The specific locus of this gradient within the primary neuron is the subject of the succeeding paper (16).